Response ff The High Frequency Long-Span Lightweight Floor Due to Human Walking: Harmonic Response Analysis - Siregar, Atur P. N. (Jurusan Teknik Sipil Universitas Tadulako, 2017)
This paper is an investigation of high natural frequency long-spanlightweigtht floor subjected to dynamicÂ footfall loading of human activities. This study was carried out to examine the vibration response of the high natural frequency long-span lightweight floor, when harmonic response analysis was applied. Acceleration root mean square (RMS) was used as a method to determine the vibration response of the high natural frequency long-span floor model. The parametric studies of natural frequency of 7 up to 20 Hz and damping ratio of 0.5% and 2% were employed to investigate the response of the model.Increasing damping ratio of the model was found to have a significant effect on reducing acceleration RMS. However, increasing natural frequency of the high natural frequency long-span lightweight floor model demonstrated to have an insensitive influence on the acceleration RMS.Â